Green synthesis and characterization of gold-based anisotropic nanostructures using bimetallic nanoparticles as seeds. Issue 46 (20th October 2021) - Nieto-Argüello, Alfonso; Torres-Castro, Alejandro; Villaurrutia-Arenas, Rafael; Martínez-Sanmiguel, Juan J.; González, María Ujué; García-Martín, José Miguel; Cholula-Díaz, Jorge L.
Abstract : Au-based anisotropic nanostructures were synthesized using starch-capped bimetallic Ag/Au nanoparticles as seeds under mild conditions. Abstract : Nanostructured noble metals are of great interest because of their tunable optical and electronic properties. However, the green synthesis of anisotropic nanostructures with a defined geometry by the systematic nanoassembly of particles into specific shape, size, and crystallographic facets still faces major challenges. The present work aimed to establish an environmentally friendly methodology for synthesizing gold-based anisotropic nanostructures using starch-capped bimetallic silver/gold nanoparticles as seeds and hydrogen peroxide as a reducing agent.